Reproductive biology of the endemic dace Telestes karsticus Marčić and Mrakovčić, 2011 (Cyprinidae, Leuciscinae), in Croatia. (8th February 2017) - Marčić, Z.; Milković, A.; Ćaleta, M.; Buj, I.; Zanella, D.; Mustafić, P.
Summary: This paper aims to establish how Telestes karsticus has adapted its reproductive behaviour to the hydrological conditions in Sušik Creek, which dries up in the summer. Initial data are provided on the reproductive biology of this endangered (EN) and endemic species of Croatia. Fish were collected at monthly intervals from July 2007 to July 2008 using a backpack electrofishing device. The spawning period lasts from late March to early May, confirmed by the gonadosomatic index (GSI) of males and egg diameter measurements. The value of GSI for both males and females is clearly cyclic, with only one maximum achieved in April. Sexual maturity is reached at an early age, with 50% becoming mature at total lengths longer than 41 mm (males) and 51 mm (females). Absolute fecundity of gravid females ranged from 201 to 3, 188 eggs and relative fecundity was 153.6 ± 33.9 eggs per gram of body mass. Average egg diameter was determined as 1.22 ± 0.23 mm. The species is lithophilous, with eggs found in nature on gravel and among rocks. Water temperature during the spawning period ranged from 7.3°C to 13.5°C, with an average of 9.8°C. The spawning period coincides with the second peak of the 30‐year‐average water level in the creek, which runs dry during the summer period.